Family Visit Implementation Maintains Human Dignity in Public Life - Resi, Hironimus; Derung, Teresia Noiman (Humaniora: Journal of Indonesia Culture and Society, 2023)
The research aimed to describe the urgency of family visits as an implementation of maintaining human dignity in social life. Currently, violence in the family has become widespread and even increased over time, and the victims of violence are generally women and children who are completely helpless. The method applied was a literature review from various sources, namely indexed journals and books with a good impact factor. Literature reviews were collected, selected, and analyzed by identifying relevant topics, recording and reviewing concepts found from various sources, and systematically compiling the results of literature reviews. The results found are that family visits have three values that can be applied to maintain human dignity: building brotherhood as social creatures in society, listening to each other, and applying security principles to maintain collective integrity and security within the family. In conclusion, family visits are very important and needed by today's society because families need to greet each other, listen, and protect each other from crime. This effort is made so that human dignity in the image of God is maintained. Advice for Christian families is that carrying out family visits at this time is very important as a form of implementation of maintaining human dignity, which is starting to be shifted due to developments in science and technology in society.Â